Imaging of Osteoarthritis by Conventional Radiography, MR Imaging, PET–Computed Tomography, and PET–MR Imaging - Hayashi, Daichi; Roemer, Frank; Guermazi, Ali (PET Clinics, 2019)
Radiography remains the first-line imaging tool to characterize structural changes of osteoarthritis (OA) in both clinical and research settings, but MRI continues to play a large role in OA research. Compositional MRI enables evaluation of the biochemical properties of joint tissues, allowing assessment of early “premorphologic” changes that cannot be depicted on conventional MRI Hybrid PET-CT and PET–MRI allow integration of high-resolution structural information on CT and MRI with metabolic information obtained from PET related to OA disease process. We describe OA imaging by means of conventional radiography, MRI PET-CT, and PET–MRI.
CRIS-Team Scopus Importer:2019-11-29
Keywords: CT; MR imaging; Osteoarthritis; PET; Radiography